Stability Analysis for Fluid Flow between Two Infinite Parallel Plates I - Mahdi Mosa; Abdo Ali (Al-Rafidain Journal of Computer Sciences and Mathematics)
A model of fluid flow with heat transfer by conduction, convection and radiation has been discussed for stability with respect to restricted parameters (k,a,r,T*) which are proportional to: wave numbers, thermal expansion coefficient, combination of many numbers (Re,Pr,Ec,Bo,W,) and the ratio of walls temperatures, respectively using numerical technique which illustrate that the stability of the system depends on the parameters T* and a. A clear picture of the flow is shown by using an analytical method.